A cooperative multi-agent system for an assembly robotic cell - Eugénio Oliveira (1996)
A multi-agent system architecture is justified here and described for the sake of its application to an assembly robotics testbed. A blackboard-based agent using a GBB/DBB facility for intra (and not inter) agent communication is presented as well as its main functionality. Cooperation between organizers and respondent agents may lead to the use of either negotiation or client/server protocols. Also some cooperative policies and involved knowledge have been studied, classified and implemented in the robotic testbed enabling sophisticated agent behavior both in terms of cooperation and local control. We also describe several scenaria where different cooperative and conflictual situations arise, in order to discuss our system behavior. A real testbed, whose agents are briefly presented, working with real-time constraints has been already implemented and tested at our laboratory.